2022
DOI: 10.3390/su14031367
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Assessment of a Diesel Engine Fueled with Various Biodiesel Blends: Polynomial Regression and Grey Wolf Optimization

Abstract: A series of tests were carried out to assess the environmental effects of biodiesel blends made of different vegetable oil, such as corn, sunflower, and palm, on exhaust and noise diesel engine emissions. Biodiesel blends with 20% vegetable oil biodiesel and 80% diesel fuel by volume were developed. The tests were conducted in a stationary diesel engine test bed consisting of a single-cylinder, four-stroke, and direct injection engine at variable engine speed. A prediction framework in terms of polynomial regr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 99 publications
0
4
0
Order By: Relevance
“…Although new vehicles models are becoming quieter, the increasing traffic volume of road traffic increases the noise emitted. Many of the city's central streets have reached traffic saturation, almost daily congested and with slower speeds throughout the day [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although new vehicles models are becoming quieter, the increasing traffic volume of road traffic increases the noise emitted. Many of the city's central streets have reached traffic saturation, almost daily congested and with slower speeds throughout the day [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Of the four possible sources of environmental noise-road traffic, rail traffic, air traffic and industrial activity, the only cause for exceeding limit values in Pitesti may be road traffic, as there is no industry in residential areas, the only railway line is far of residential areas and the airport does not exist [21]. Therefore, as the only source of noise that exceeds the limit levels set by European legislation [2,26] is road traffic, the reduction of ambient noise can only be achieved by reducing road noise, both at the source (emitted noise) and at the receiver (mixed noise-perceived by the inhabitants).…”
Section: Introductionmentioning
confidence: 99%
“…Also, most of the researchers in this field agreed that when using biodiesel mixtures, there is a decrease in the braking thermal efficiency compared to normal diesel, and the reason is the characteristics of biodiesel that characterize it. Alahmer et al 21 in their study of a diesel engine with the use of biodiesel mixtures, they confirmed a decrease in the braking thermal efficiency. The reason for the decrease is due to the high viscosity, high density, and low calorific value compared to normal diesel…”
Section: Resultsmentioning
confidence: 87%
“…The purpose of this is to emulate the behavior of specific organisms (particles/agents/solutions) in order to achieve the optimal goal (position/location/target) based on the interaction relationship between these organisms. Formulating the mathematical equations that imitate these relationships frequently results in an optimization method [48].…”
Section: Runge Kutta Optimizermentioning
confidence: 99%